The Dynamics of Returns to Education in Kenyan and Tanzanian Manufacturing. - Söderbom, M; Teal, F; Wambugu, A; Kahyarara, G (GPRG, 2005)
We use micro data on manufacturing employees in Kenya and Tanzania to estimate returns to education and investigate the shape of the earnings function in the period 1993-2001. In Kenya, there have been long-run falls in the returns to education while for Tanzania there is evidence of rising returns in the 1990s. The earnings functions are convex for both countries and this result is robust to endogeneity. Convexity may be part of the explanation as to how rapid expansion of education in Africa has generated so little growth if expansion has been concentrated at lower levels of education.